Comparison of Alemtuzumab and Anti-thymocyte Globulin Treatment for Acute Kidney Allograft Rejection - van der Zwan, Marieke; Clahsen-Van Groningen, Marian C.; van den Hoogen, Martijn W. F.; Kho, Marcia M. L.; Roodnat, Joke I.; Mauff, Katya A. L.; Roelen, Dave L.; van Agteren, Madelon; Baan, Carla C.; Hesselink, Dennis A. (Frontiers in Immunology, 2020)
Rabbit anti-thymocyte globulin (rATG) is currently the treatment of choice for glucocorticoid-resistant, recurrent or severe acute allograft rejection (AR). However, rATG is associated with severe infusion-related side effects. Alemtuzumab is incidentally given to kidney transplant recipients as treatment for AR. In the current study, the outcomes of patients treated with alemtuzumab for AR were compared with that of patients treated with rATG for AR. The patient-, allograft-, and infection-free survival and adverse events of 116 alemtuzumab-treated patients were compared with those of 108 patients treated with rATG for AR Propensity scores were used to control for differences between the two groups. Patient- and allograft survival of patients treated with either alemtuzumab or rATG were not different (hazard ratio [HR] 1.14, 95%-confidence interval [CI] 0.48-2-69, p=0.77, and HR 0.82, 95%-CI 0.45-1.5, p=0.52, respectively). Infection-free survival after alemtuzumab treatment was superior compared with that of rATG-treated patients (HR 0.41, 95%-CI 0.25-0.68, p<0.002). Infusion-related adverse events occurred less frequently after alemtuzumab treatment. Alemtuzumab therapy may therefore be an alternative therapy for glucocorticoid-resistant, recurrent or severe acute kidney transplant rejection.